HOTS LEARNING IN PANDEMIC OF COVID-19 PERIOD THROUGH DEEP LEARNING MODEL - Heti Aisah (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2020)
Covid-19 pandemic has not shown a drastic decrease in trend, so it is estimated that the new school year 2020-2021 students will continue to carry out their learning processes from home, or Learning from Home. A survey conducted by the Ministry of Education and Culture's directorate's assessment department, related to Learning from Home students in March, showed that 29% of students lack enthusiasm, 28% thought it was normal, which stated Learning from Home was pleasant 26%, 10% burdensome, and 7% others (boring, tiring, not communicative, not active). The condition needs to be sought a solution, one of the alternatives offered is the teacher or education unit using the strategy of learning activities Deep Learning. DEL is a process of learning activities that optimize and activate the work of the brain so that students do not experience boredom, and not excited. The final stage DEL is included in the domain of analysis and creates, allowing students to develop higher-order thinking skills or High Order Thinking Skills (HOTS).